Management of cystic diseases of the pancreas - Hakan Şentürk, (Turkish Journal of Gastroenterology, 2019)
Pancreatic cysts are challenging to the gastroenterologist. Detection rate is increasing and neither criteria for a definitive diagnosis,  nor a validated surveillance strategy is available. Pancreatic endosonography with or without sampling is necessary in most of the cases. However this technique requires expertise and is not widely available. While some cysts have a malignant potential or already malign at the diagnosis, most are benign and remain so for decades. We are going to review the existing data on this controversial subject. Not too distant, just thirty years ago pancreatic cysts (PC) were considered so rare deserving publication (1). Nowadays, it is one of the most frequent abdominal incidental finding challenging gastroenterologists. Thanks to the progress in imaging technology, we are able to detect cysts as small as a few millimeters in the pancreas. The presence of pancreatic disease implies a negative connotation, for public and the involved subject is exposed to a great deal of anxiety after this diagnosis. Given to the absence of clearly established methods in approaching this condition, the gastroenterologist, sometimes, may fall short of relieving this anxiety. In the following chapter we are going to summarize the hitherto data in the diagnosis and management of this emerging disease.